Novel linear megaplasmid from Brevibacterium sp. isolated from extreme environment - Dib, Julian Rafael (2010)
Brevibacterium sp. Ap13, isolated from flamingo's feces in Laguna Aparejos, a high-altitude lake located at approximately 4,200 m in the northwest of Argentina was previously found to be resistant to multiple antibiotics, and was therefore screened for plasmids that may be implicated in antibiotic resistance. Brevibacterium sp. Ap13 was found to contain two plasmids of approximately 87 and 436 kb, designated pAP13 and pAP13c, respectively. Only pAP13 was stably maintained and was extensively characterized by pulsed-field gel electrophoresis to reveal that this plasmid is linear and likely has covalently linked terminal proteins associated with its 5' ends. This is the first report of a linear plasmid in the genus Brevibacterium and may provide a new tool for genetic manipulation of this commercially important genus.